2019
DOI: 10.1155/2019/9675450
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 Inhibitor SNX-2112 Enhances TRAIL-Induced Apoptosis of Human Cervical Cancer Cells via the ROS-Mediated JNK-p53-Autophagy-DR5 Pathway

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a potent cancer cell apoptosis-inducing factor that can induce apoptosis in a variety of cancer cells. However, resistance to TRAIL in cancer cells is a huge obstacle in creating effective TRAIL-targeted clinical therapies. Thus, agents that can either enhance the effect of TRAIL or overcome its resistance are needed. In this study, we combined TRAIL with SNX-2112, an Hsp90 inhibitor we previously developed, to explore the effect and mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 86 publications
(97 reference statements)
0
24
0
Order By: Relevance
“…Reactive oxygen species (ROS) are active compounds that generally contain oxygen and result from aerobic metabolism [4]. In the past, ROS were generally thought to be merely toxic by-products of aerobic metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are active compounds that generally contain oxygen and result from aerobic metabolism [4]. In the past, ROS were generally thought to be merely toxic by-products of aerobic metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have indicated that JNK/c-Jun signaling pathway that belongs to mitogen-activated protein kinase (MAPK) pathway, has vital function in regulating autophagic cell death. For example, Bai, Y. et al have reported that PDIA6 knockdown suppressed NSCLC cell proliferation and increased cisplatininduced autophagic cell death via interacting with MAP4K1 to activate the JNK/c-Jun signaling pathway [43]; Hu, L. et al have proved that SNX-2112, the Hsp90 inhibitor, enhanced TRAIL-induced apoptosis and autophagy of cervical cancer cells through activating the ROS-regulated JNK-p53-autophagy-DR5 pathway [32]; Zhu, Q. et al indicated that irinotecan (IRI) stimulated the reactive oxygen species (ROS)related JNK-and p38-MAPK signaling pathways to increase autophagy-dependent apoptosis and inhibit growth of gastric cancer cells [44]. Therefore, the active status of the JNK/c-Jun signaling pathway was detected under CASK knockdown condition in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies have con rmed that JNK pathway activation plays a pivotal role in regulating autophagy, and is closely related with chemoresistance and tumor progression [32][33][34]. To further investigate the mechanism of CASK knockdown-induced autophagy, the effect of CASK knockdown on the JNK pathway was detected.…”
Section: Hypomethylation-associated Upregulation Of Cask Expression Imentioning
confidence: 99%
“…Hsp90 affects the expression and function of more than 100 client proteins, such as Akt, Raf-1, Cdk4, MMP2, and VEGFR2, which regulate cancer cell proliferation, invasion and angiogenesis. 22 The Hsp90 inhibitor, SNX-2112, has been shown to exert antitumor effects on a variety of tumors. However, therapeutic doses of SNX-2112 can also exert significant off-target toxicity.…”
Section: Discussionmentioning
confidence: 99%